Keanekaragaman Jenis Ikan di Perairan Lebak Jungkal Kecamatan Pampangan Kabupaten Ogan Komering Ilir pada Musim Hujan dan Kemarau - Mohammad Rasyid Ridho; Enggar Patriono; Rita Haryani (Fakultas Biologi | Universitas Jenderal Soedirman, 2019)
The research about fishes diversity in Lebak Jungkal waters in Pampangan District Ogan Komering Ilir Regency in rainy and dry season was conducted on February till July 2013. The aim of this research were to analyzed diversity index and Evenness index of fishes in Lebak Jungkal in rainy and dry season. Fish samples were collected using purposive random sampling method. The obtained samples were count for species and individual number of each species as a basis for estimating the diversity and evenness indexes. During rainy season, as much as 3,406 fish individuals were caught and were identified into 17 fish species, while a sum of 2,019 individuals were collected in dry season and were placed into 14 fish species. The result of diversity index (H’) categorized intermediet and diversity index (H’) in dry season (0.142-1.754) was lower than rainy season (1.862-2.008). Otherwise, Evenness index (E) in dry season (0.566-0.604) more evenly distributed than rainy season (0.061-0.625).